Induction of phosphatase shatterproof 2 by evodiamine suppresses the proliferation and invasion of human cholangiocarcinoma. (March 2019) - Zhu, Biqiang; Zhao, Lei; Liu, Yang; Jin, Ye; Feng, Jing; Zhao, Fuya; Sun, Jiayu; Geng, Rui; Wei, Yunwei
Abstract: Cholangiocarcinoma (CCA) is one of the most common fatal carcinomas and is well known to be lack of effective treatment. Thus, novel therapeutic strategies are greatly needed. Evodiamine, a quinozole alkaloid isolated from evodia rutaecarpa Bentham, has been demonstrated to exhibit anti-tumor effects on many cancer cells. However, little is known in terms of the effects on cholangiocarcinoma. In this study, we studied whether this traditional Chinese Medicine could serve as new potential therapeutic drugs to treat CCA. We discovered that evodiamine inhibited CCA cell proliferation and induced apoptosis. Moreover, evodiamine inhibited CCA cell migration and invasion. Mechanistically, our studies demonstrated that evodiamine inhibited the activation of IL-6 -induced STAT3 signaling activation, and the inhibitory effect was likely due to the upregulation of phosphatase shatterproof 2 (SHP-2), a negative feedback regulator of IL-6/STAT3. Blockage of SHP-2 through small interference RNA (siRNA) abolished the evodiamine -induced IL-6/STAT3 signaling inhibition. Moreover, in vivo experiment showed evodiamine inhibited the tumor growth of nude mice bearing TFK-1 xenografts. In summary, our results implied evodiamine as a promising anti-cancer agent in the treatment of CCA, and the mechanism is likely due to the inhibition of IL-6/STAT3 signaling with upregulating the expression levels of SHP-2.